High Burden of Adverse Drug Reactions to Isoniazid Preventive Therapy in People Living With HIV at 3 Tertiary Hospitals in Uganda: Associated Factors. (1st February 2022) - Nanyonga, Stella Maris; Kitutu, Freddy Eric; Kalyango, Joan; Frank, Mulindwa; Kiguba, Ronald
Abstract : Background: HIV is one of the most important risk factors of tuberculosis (TB)-related morbidity and mortality. Isoniazid preventive therapy (IPT) is recommended to prevent latent TB reactivation in patients with HIV. However, due to multiple therapies and comorbidities, these patients are predisposed to adverse drug reactions (ADRs) that lead to increased morbidity and mortality. The aim of this study was to determine the prevalence and associated factors of suspected IPT-linked ADRs in HIV-positive patients using IPT. Methods: A cross-sectional study was conducted between February and March 2020 at 3 regional referral hospitals (RRHs) in central Uganda. We sampled 660 HIV-positive patients aged 10 years or older who received IPT between July and December 2019 inclusive. Patients were interviewed using a pretested structured questionnaire, and their treatment records were reviewed. A modified Poisson regression model with clustered robust standard errors was used to identify factors associated with suspected IPT-linked ADRs. Results: The prevalence of the suspected ADRs was 51% (334 of the 660; 95% confidence interval [CI]: 18% to 83%). Patients self-reported 7-fold the number of suspected ADRs documented in the clinical files by the health care workers. Musculoskeletal symptoms were the most frequently experienced reaction (14%), followed by dizziness (13%) and peripheral neuropathy (11%). Serious suspected ADRs were experienced by 12% of the study participants; the most common were hepatotoxicity (26%), dizziness (23%), and neuropathy (17%). Female sex (aPR [adjusted prevalence ratio]: 0.92, 95% CI: = 0.88 to 0.95), study site (aPR: 1.09, 95% CI: = 1.09 to 1.18), level of education (aPR: 0.94, 95% CI: = 0.94 to 0.99), history of TB (aPR: 0.93, 95% CI: = 0.87 to 0.99), good IPT adherence (aPR: 1.16, 95% CI: = 1.05 to 1.29), and use of protease inhibitor (PI)-based antiretroviral therapy (aPR: 1.01, 95% CI: = 1.00 to 1.02) were significantly associated with suspected IPT-linked ADRs. Conclusion: The prevalence of suspected IPT-linked ADRs is high, and hepatotoxicity is the most commonly reported serious suspected ADR. Patients self-reported more suspected ADRs than those documented in clinical files by health care workers. Patient engagement could improve ADR detection and potentially strengthen the pharmacovigilance system. Patients with a high risk of ADR ought to be monitored regularly to enable early detection and management.